Personal Data Monetisation Strategy: Systematic Review and a Case Study of UAE - Al Falasi, Reem Jr (2019)
Governments are always looking for an improved vision which enhances construction of citizens’ quality of life. This vision can be achieved through governmental data monetisation to determine citizens’ challenges and demands. The monetisation procedure will lead to reduction of the city’s expenses, inspire innovation, and encourage economic growth. However, currently, there is a lack of a practical governmental data strategy or related processes and platforms. Furthermore, data providers have several concerns regarding their shared data, as they have no control over or ownership rights to it. This purpose of this study is to 1) to investigate the elements necessary to build a targeted governmental data monetisation strategy, 2) explore the existing personal data monetisation procedures, and 3) recognise data providers’ awareness of their data monetisation and the economic growth of this process in the UAE. The concept has been explored in order to answer the study’s research questions though the literature review, systematic review of 182 works of research published between 2002 and 2019, and the UAE case study, which collected 225 responses from the conducted survey to investigate data providers’ willingness to share their data and their knowledge of their data’s commercial value. The key findings indicate that data providers require a trusting and confidential relationship with the data consumers, who monetise data from the business entities, and maintain the data providers’ privacy and provide efficiency benefits across different entities. Future study will explore the governmental data monetisation strategy of a specific organisation in the UAE in addition to investigating the monetisation procedure from the data consumer’s point of view.